The Synchronization Of Timetable By Having Minimum Transfer Time Without Considering The Waiting Time - Puspania Okpatiasari*; Erika Buchari; Melawaty Agustien (Riwayat: Educational Journal of History and Humanities, 2023)
Light Rail Transit (LRT)  is planned to be main public transportation or backbone in Palembang City and being supported by its feeder bus, Teman Bus. LRT and Teman Bus in Palembang City do not have an integrated timetable. LRT have been operating for almost five years with fix timetable. However, Teman Bus does not have timetable. Based on the theory, integration is one of  the way to create a good public transport service. This paper aimed creating Teman Bus timetable based on real condition of journey time data distribution method with case study in 2021. Some schemes which are made by passangers will be used to optimize the timetable. This scheme will effect the walking time. Then, Teman Bus timetable will be synchronized with existing Light Rail Transit timetable. These synchronization will create an integrated timetable without waiting time. This methode is used because there is only one type vehicle and one type of route.